Communicative Aspect of Educational Process as a Category of Non-Classical Paradigm of Creativity - A. A. Kartashova (Russian State Vocational Pedagogical University, 2015)
The article considers the urgent problems of modern education related to creative consciousness development and acceptable imitation proportion. The author refers to the communication theory to show the interrelation between creativity and communicative processes. The overview and analysis of a number of studies including G.Lassvell's formula and Y.M. Lotman's semiotic system prove that the communication category directly influences the logic of personal development. The main emphasis is on J. Habermas' theory with its core concept of rational communication procedure and accumulation of knowledge by means of moral consciousness. Habermas singles out six stages of moral judgment: two pre-conventional (interaction controlled by authority and interest-driven cooperation); two conventional (role action and interaction driven by norms); post-conventional; and discursive. The author makes a conclusion that creativity is based on both the originality of creative action itself, according to the classical paradigm, and cooperation between the author and creative product consumer: e.g. writer and reader, teacher and student, etc. The research findings can be used in further studies of communicative relations in educational sphere and in practical teaching.